Socio-economic conditions of rural Georgian households and their behavioral intentions regarding tourism development : an empirical analysis - Heiny, Jennifer; Justus Liebig University Giessen (My University, 2017)
This research examines socio-economic living conditions of the population in two mountainous regions in Georgia. Household data and data regarding intended behavior of private households intentions to enhance their (or start) activities in the tourism sector is analyzed with structural equation models.A descriptive analysis of the household data shows that animal husbandry and the cultivation of potatoes are more common in the Kazbegi region than in the Borjomi region. There is a discernible difference between the two main villages and smaller villages. Agricultural activities are slightly higher in the smaller villages and self-employment in agriculture is an important source of income. Touristic activities are more prominent in the main villages. Diversification of income sources in the sense of being active in both agriculture and tourism is stronger in the main villages than in the smaller villages. Comparing the smaller villages to the main villages, it shows that their income is particularly low, but in comparison to other parts of Georgia the income of the main villages is also low.The Theory of Planned Behavior (TPB, Fishbein & Ajzen 2010) serves as the theoretical framework for the analysis of intentions to start or enhance activities in the tourism sector. According to the TPB, three latent constructs influence intention to carry out a certain behavior. The basic model provides evidence for significant influences from subjective norm (i.e. the respondent s perceived approval of the behavior from others) and perceived behavioral control (i.e. the respondent s felt ability to carry out the behavior) on the intention to enhance tourism supply within the next year. This is in accordance with the TPB. However, the model could not prove that the respondent s attitude towards the behavior (the theory s third construct) significantly influences intention.A special feature of this research is the inclusion of belief-based measures. The analysis of beliefs reveals that in the case of subjective norm, family , friends and neighborhood are the most important referent groups while the respondents do not look for the government s approval. In the case of perceived behavioral control, likelihood of bank loans and feeling ill or tired significantly influence the construct. So to improve conditions for private households to start or enhance working in the tourism sector, credits should be granted and mechanisms for times of illness need to be installed. The fact that no significant influence from attitude on intention was found and subjective norm has the strongest standardized influence is not in line with many other studies that have used the TPB. It shows that the cultural background differs from that of the majority of studies with the TPB; they concentrate on Western societies. This study provides evidence for the fact that the TPB can also be applied in collectivist cultures but with a shift in the importance of the latent explanatory constructs.A modification of the model was tested to see if perceived behavioral control moderates the influence of attitude and subjective norm on intention (Yzer 2007). A moderation effect cannot be confirmed, but it is possible that the sample was too small to detect a significant effect since statistical power is low.The integration of experience in the tourism sector as a background variable shows a mediated influence from experience on intention. The constructs subjective norm and perceived behavioral control and the belief family mediate the influence of experience on intention: the more experience a household has in the tourism sector, the more favorable is the subjective norm, the higher is the perceived control and the more positive is the perceived support from the family towards enhancing such activities and in consequence the higher is the intention of doing so.Altogether the analyses show that households in both research areas use agricultural activities mainly for subsistence purposes with only some exceptions of households that sell part of their production. The tourism sector offers another opportunity for income. In order to facilitate households intentions to become active or enhance activities in this sector, programs should foster affordable credits along with a support system in cases of illness while taking into account the social surrounding of households. It has to be kept in mind, though, that tourism is not an option for everyone: especially in smaller and secluded villages the number of tourists is slim to none. On the other hand, a better offer for tourists could lead to more tourists which can also create more opportunities for work in other sectors.

Die vorliegende Dissertation ist im Rahmen des von der VolkswagenStiftung finanzierten, interdisziplinären Forschungsprojekts Analysing multiple Interrelationships of Environmental and Societal Processes in Mountainous Regions of Georgia (AMIES) an der Justus-Liebig-Universität Gießen entstanden. Sie betrachtet auf der einen Seite die sozioökonomischen Lebensbedingungen von Privathaushalten in zwei montanen Regionen (i.e. Kazbegi und Borjomi) im Kaukasus in Georgien. Auf der anderen Seite wird mithilfe der Theorie des geplanten Verhaltens (TPB, Fishbein & Ajzen 2010) analysiert, welche Faktoren sich auf die Verhaltensabsicht privater Haushalte auswirken, inner¬halb des nächsten Jahres im Tourismus aktiv zu werden, oder entsprechende Aktivitäten auszubauen.Eine deskriptive Analyse quantitativer, selbsterhobener Daten zeigt, dass in Kazbegi mehr private Haushalte landwirtschaftliche Aktivitäten zur Subsistenzwirtschaft nutzen als in Borjomi. In beiden Regionen sind diese Aktivitäten in den kleinen Dörfern ausgeprägter als in den jeweiligen Hauptorten, während wiederum touristische Aktivitäten stärker in den Hauptorten auftreten. Im Vergleich zum Rest Georgiens sind die Lebensbedingungen in beiden Regionen eher schlecht.Das Strukturgleichungsmodell der TPB, die hauptsächlich in westlichen Industrie¬gesellschaften angewendet wird, bestätigt bis auf eine Ausnahme die postulierten Hypothesen, was mit der Stichprobe eines post-sowjetischen Landes zusammenhängen könnte. Die selten empirisch modellierte Integration der Beliefs in Form von MIMIC-Konstrukten gibt Aufschluss darüber, dass bezahlbare Kredite, Schutzmechanismen für Ausfälle und insbesondere Familie und Freunde jeweils mediierte Einflüsse auf die Verhaltensabsicht der Privathaushalte ausüben und liefern Ansatzpunkte für mögliche Interventionen. Als weitere Besonderheit wurde getestet, ob die wahrgenommene Verhaltenskontrolle den Einfluss der übrigen Konstrukte auf die Verhaltensabsicht moderiert (Yzer 2012). Die vorliegenden Daten bestätigen dies nicht, allerdings könnte die kleine Stichprobe nicht genügend Power für einen solchen Test haben. Die Aufnahme von Erfahrung als Hintergrundvariable zeigt, dass diese einen mediierten Einfluss auf die Verhaltensabsicht ausübt. Je erfahrener ein Haushalt ist, desto eher zeigt er die Absicht, touristische Aktivitäten auszubauen.Insgesamt zeigen die Analysen, dass die Haushalte in beiden Regionen ihre landwirtschaftlichen Erzeugnisse hauptsächlich zur Subsistenznutzung verwenden. Der Tourismussektor bietet eine weitere Einkommensquelle. Um Haushalten den Einstieg oder Ausbau von Aktivitäten im Touris-mussektor zu erleichtern, sollten bezahlbare Kredite sowie ein Schutzmechanismus im Krankheitsfall bereitgestellt werden, wobei immer das soziale Umfeld der Haushalte zu berücksichtigen ist. Gleichzeitig darf nicht vergessen werden, dass Tourismus nicht für jeden Haushalt eine Option darstellt: Insbesondere kleine, abgeschiedene Dörfern sind keine klassischen Touristendestinationen.
Keywords: Empirische Analyse; Theorie des geplanten Verhaltens; Strukturgleichungsmodellierung; Haushaltsdaten; Mediation / Moderation; empirical analysis; Theory of Planned Behavior; structural equation modeling; household data; mediation / moderation; ddc:300